Intelligent model-based feedback: Helping learners to monitor their individual learning progress - Ifenthaler, Dirk (2011)
Automated knowledge assessment methodologies provide the technological background for producing instant feedback at all times during the learning process. It is expected that the availability of such individual, dynamic, and timely feedback supports the learner's self-regulated learning. This chapter provides the theoretical background for an intelligent feedback approach and introduces two automated model-based feedback tools: TASA (Text-Guided Automated Self Assessment) and iGRAF (Instant Graphical Feedback). The chapter concludes with a discussion of the two feedback approaches and future research directions. © 2012, IGI Global.